The Influence Of Product Quality, Service Quality, And Store Atmosphere On Repurchase Decisions With Customer Satisfaction As An Intervening Variable At Atap Langit Cafe Semarang - Juniyanto, Aditya; Prabowo, Heri; Sijabat, Rauly (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This research is inspired by the failure to meet the revenue target of Atap Langit Cafe Semarang in February. Currently, cafes are indeed one of the favorite places to visit for people from various age groups, from children to adults. Atap Langit Cafe is quite well-known in Semarang but is experiencing a drop in revenue and failed to meet the revenue target. Therefore, this study was created to determine the effect of product quality, service quality and store atmosphere on repurchase decisions with customer satisfaction as an intervening variable. This study uses a quantitative method with a sample size of 100 respondents. The sampling technique used was purposive sampling using the SmartPls tool as a testing tool. The results of this study indicate that the variables of product quality and customer satisfaction have an effect on repurchase decisions. Service quality and store atmosphere have no effect on repurchase decisions. Product quality, service quality and store atmosphere have an effect on customer satisfaction but all of them have no effect on repurchase decisions mediated by customer satisfaction.